OPTIMIZATION OF TRAINING PROGRAM DEVELOPMENT FOR REMOTELY PILOTED AIRCRAFT OPERATORS IN THE SPHERE OF BORDER SURVEILLANCE - Islamova, Oleksandra; Hrishko-Dunaievska, Valentyna; Biliovskyi, Oleksandr; Kulagin, Oleksandr; Hnydiuk, Oleksandr; Miroshnichenko, Valentyna (Revista Inclusiones, 2021)
The study reveals the theoretical and practical approaches of developing training programs for Remotely Piloted Aircraft operators in the sphere of border surveillance of the state border protection agencies of the European Union and Ukraine using multicriteria optimization to find required rational parameters. According to the developed methodology, using the multicriteria optimization method provides an opportunity to choose a program for training such specialists, which will best meet the objectives and peculiar needs of the state border protection agencies of the European Union and Ukraine. The results of the study within the educational grant of Frontex Agency conducted by the team of experts from the Border Guard Services of Ukraine and EU countries were used to enhance the training program of air reconnaissance units of border protection bodies at the Main Training Centre of the Border Guard Service of Ukraine based on the best EU practices, in order to ensure obtaining of knowledge and practical skills by personnel of the border guard Remotely Piloted Aircraft external crews, which will increase the level of interoperability and professional competence of border guards while conducting border surveillance tasks.